(untitled) (Indian Journal of Arid Horticulture, 2013)
The experiment was carried out at the farmers’ field at Nimoda and Ummedpura villages, Jhalrapatan, Jhalawar during the year 2009-10. Declining plants of Nagpur Mandarin were subjected to different time of top working. It was observed that mid October time of budding as a part of top working on beheaded plants had significantly better effect on budding performance and growth. Maximum bud take per cent (75.80 %), minimum days required to first sprouting (18.27 days), minimum days required to 50 per cent sprouting (53.26 days) and the maximum budding success (70.23 %) were recorded in mid October budding time. Under this treatment maximum length of sprout shoot (14.19 cm), diameter of sprout shoot (4.97), number of nodes (11.04), length of internodes (1.29), plant height (31.01 cm) number of leaves on sprout shoots (15.23), leaf area (15.23 cm ), perimeter of leaves (20.25 cm) and chlorophyll content (3.704 mg/g) were noted.